2014
DOI: 10.1890/es14-00109.1
|View full text |Cite
|
Sign up to set email alerts
|

Weak growth response to nitrogen deposition in an old‐growth boreal forest

Abstract: Citation: Du, E., and J. Fang. 2014. Weak growth response to nitrogen deposition in an old-growth boreal forest.Ecosphere 5(9):109. http://dx.doi.org/10.1890/ES14-00109.1Abstract. Nitrogen (N) deposition has been enhanced globally due to the dramatic increase in anthropogenic N emissions, but the effects of N deposition on the growth of old-growth forests remain poorly understood. A three-year N enrichment experiment (0, 20, 50 and 100 kg N ha À1 yr À1) was conducted in an old-growth boreal forest in Northeast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 53 publications
3
16
0
Order By: Relevance
“…The responses of leaf P concentrations to N deposition vary among studies, with reported increases (Huang et al 2012, Lü et al 2013), decreases (Sardans et al 2016), or neutral responses (Chen et al 2015). Consequently, N addition could cause an increase in the N:P ratio (You et al 2018), thus further intensifying P limitation (Du and Fang 2014) and even shifted from N limitation toward P limitation. In addition to N and P, K, Ca, and Mg are also essential nutrients for plant metabolism (Watanabe et al 2007, Tian et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The responses of leaf P concentrations to N deposition vary among studies, with reported increases (Huang et al 2012, Lü et al 2013), decreases (Sardans et al 2016), or neutral responses (Chen et al 2015). Consequently, N addition could cause an increase in the N:P ratio (You et al 2018), thus further intensifying P limitation (Du and Fang 2014) and even shifted from N limitation toward P limitation. In addition to N and P, K, Ca, and Mg are also essential nutrients for plant metabolism (Watanabe et al 2007, Tian et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Boreal forests have been shown to be very sensitive to N deposition (Makipaa 1998, Strengbom et al 2002), and as such, external N inputs are expected to release plants from N limitations, although they might alter the nutrient stoichiometry by changing the ratios of N to other elements. In an old‐growth boreal forest in Northeast China, short‐term (three‐year) N addition increased the leaf N contents in trees and understory plants and induced N and P imbalances in canopy trees (Du and Fang 2014, Du 2017). Based on the results of a six‐year N‐enrichment experiment at the same site, the present study explores the long‐term effects of simulated N deposition on leaf nutrient concentrations and the leaf stoichiometry at the community level (including dominant tree and understory plants).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing atmospheric nitrogen (N) deposition is one of the most important global changes (Galloway et al, ; Gruber & Galloway, ), which can alter ecosystem nutrient cycling (Deng et al, ; Lucas et al, ; Zhang et al, ). Changes in concentrations of foliar nutrients, which are an important part of nutrient cycling, can reflect plant nutrient status and nutrient acquisition mechanisms (Han et al, ; Mao et al, ), and they have been widely studied in the past few decades (Bauer et al, ; Du & Fang, ; Elvir et al, ; Flückiger & Braun, ; You et al, ). However, most of these previous studies have focused only on the responses of plant N, phosphorus (P), and N:P ratio to N addition (Sardans et al, ; You et al, ; Yue et al, ), and our understanding of the effects of N addition on other foliar nutrients is limited.…”
Section: Introductionmentioning
confidence: 99%
“…This response results in faster biomass accumulation, which produces taller, skinnier trees [52]. Although this is more likely to affect young trees or seedlings exposed to elevated N, Du and Fang [53] also found weak growth in a mature forest. This may increase the mortality of young trees as a result of light limitation or the respiratory costs of early rapid growth [52].…”
Section: Observations Of N Impactsmentioning
confidence: 99%